The Effect of Taxation Understanding, Religiosity, and Machiavellianism on Individual Taxpayer Compliance Who Perform Freelance Job in Dki Jakarta - Mamentu, Hutria Angelina; Utami, Wiwik (Archives of Business Research, 2021)
This research is the first conducted using the population of individual taxpayers who do freelance job in DKI Jakarta. This research sought to examine the effect of Taxation Understanding, Religiosity, and Machiavellianism on Individual Taxpayer Compliance in DKI Jakarta. This research made use of primary data obtained through questionnaire. There were 185 research samples tested and analyzed using SmartPLS version 3.3.3. The research results revealed that taxation understanding and religiosity have significant effect on individual taxpayer compliance. On the other hand, Machiavellianism has no significant effect on individual taxpayer compliance.